2021
DOI: 10.5114/wo.2021.112234
|View full text |Cite
|
Sign up to set email alerts
|

Mutational landscape of primary and recurrent Ewing sarcoma

Abstract: Introduction: Ewing sarcoma (ES) is a highly aggressive malignancy of bone and soft tissues characterized by the presence of a genetic fusion involving the EWSR1 gene. More than one-third of patients develop distant metastases, which are associated with unfavorable prognosis. Knowledge about the disease's genetic landscape may help foster progress in using targeted therapies in the treatment of ES. Aim of the study: The objective is to assess the mutational landscape of ES in pretreatment samples, tumor sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Studies have reported that the most common mutations in Ewing sarcoma are the loss of function of STAG2, TP53, and CDKN2A genes [15]. Moreover, some studies have also indicated that PIK3R1, NOTCH1, and CREBBP are common in recurrent Ewing sarcoma [16]. The functional changes of TP53, PMS2, and RET genes are also important factors in inducing Ewing sarcoma [17].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported that the most common mutations in Ewing sarcoma are the loss of function of STAG2, TP53, and CDKN2A genes [15]. Moreover, some studies have also indicated that PIK3R1, NOTCH1, and CREBBP are common in recurrent Ewing sarcoma [16]. The functional changes of TP53, PMS2, and RET genes are also important factors in inducing Ewing sarcoma [17].…”
Section: Discussionmentioning
confidence: 99%
“…Sarcomas typically have reoccurring driver genomic events, covering amplification, mutations, or translocations (Baumhoer et al, 2019;Jagodzinska-Mucha et al, 2021;van der Graaf et al, 2022). For instance, undifferentiated sarcomas frequently undergo recurrent copy number mutations, and deletions of oncogenes, such as TP53, RB1, CDKN2A, and CDKN2B, are common (Hames-Fathi et al, 2022).…”
Section: Discussionmentioning
confidence: 99%